Leadership of international schools and the International Baccalaureate learner profile. (September 2019) - Gardner-McTaggart, Alexander
Purpose: this study offers a rare insight into senior leadership in International Baccalaureate (IB) international schools. The IB international school profits from the perceived quality and consistency of the IB brand; international schools, however, suffer from an endemic culture of change and reinterpretation. The IB learner profile (IBLP) offers scope for consistency and an overarching ethos, and research finds that 'buy-in' to the IBLP and modelling of it in all aspects of school life are essential in achieving this. It emerges that buy-in to the IBLP in directors is split between the personal and the operational. Research method: This interpretive study explores IB directors in multiphase research over two years employing an aspect of critical phenomenology through the lens of the IBLP and Global Citizenship Education (GCE). Findings: Only one in six directors uses the IBLP in leadership. Generally, directors attribute the IBLP a junior status. Analysis through Bourdieu finds IB directors have higher loyalty to (loosely defined) GCE through their Christian values. A foregrounding of individual values over the secular IBLP places IB directors as primary catalysts for the change culture unravelling the consistency of the IB international school, confirming the value of the IBLP in leadership.